GERAKAN HIZBUT TAHRIR DAN RAELITAS POLITIK ISLAM KONTEMPORER DI INDONESIA - Jonkennedi, Jonkennedi (Fakultas Dakwah IAIN Purwokerto, 2012)
In Post-New Order, the process of democratization is not only marked by theemergence of new political parties and the blooming of civil society groups, but alsogroups that identify themselves as part of a religious movement. Islam in particularexplicitly identifies the community groups that are manifest at the same time positioning itas the basis for the orientation of the movement and its struggle.The emergence of groups affiliated with Islam restored the old debate being acontroversy foe a long time. The issue is what the most representative formulation of Islamand state is. There are 2 (two) major currents in this discourse which are then plotted on agroup of formalists and substantialists. Formalist groups have an interest in linking Islamand the state legally and formally, whereas substantialist groups emphasize on thesubstantial meaning of Islam in the state.This paper will discuss a pattern of Islam formalist movement in the politicalrealities of contemporary Indonesia. The democratization process enables the various civilsociety groups to express their aspirations through the organizing group. One of theaspirations that are organized as part of civil society is a political movement. Formalpolitical institutions in the development of democracy continue to decline or deficit. Otherforms of political organizing on the one hand can be interpreted as a deepening ofdemocracy or of deliberation, but on the other hand, it can be interpreted as an expressionof dissatisfaction to the formal political representation.